PROHIBITION OF ANGULAR AND DISTANCE MEASUREMENT ERRORS OF ELECTRONIC TAXIMETERS, WHICH ARE WIDELY USED IN UZBEKISTAN - Abdisaidovich, Mirzaev Anvar; Kamola, Rakhmatilloeva (International Journal of Psychosocial Rehabilitation, 2020)
This article analyzes the results of the study of two electronic taximeters (angle and distance without reflectors) included in the fleet of geodetic instruments of Uzbekistan, ie errors in measuring angles and distances, and develops recommendations as a result. The research methods developed for electronic tachometers allow the user to evaluate its accuracy in measuring angles and distances without reflectors under production conditions, selecting the instrument that best suits the type of project.